(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This scientific article reviews social inequality as a complex theoretical, historical, and literary phenomenon. The investigation covers the concept and definition of social inequality, its philosophical roots in classical and Enlightenment thinking, and its elaboration in the context of major historical processes. Particular attention is paid to the contribution of Plato, and to the ideas of Jean–Jackques Rousseau`s “Discourse on the Origin and Basis of Inequality Among Men” (1755), which conceptualized inequality as man- made. From the literary perspective, the research then examines the ways social inequality has been represented and criticized in world literature, mainly through the traditions of realism and humanitarianism. Author such as Charles Dickens is considered as who reflected poverty, injustice, and lives of living on the margins of society. In this way, the study illustrates that literature is an effective medium for the denunciation of social injustice, the shaping of moral consciousness, and the contestation of unequal social structures.